PENGARUH KUALITAS LAYANAN, CITRA PERUSAHAAN, PERSEPSI HARGA, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUASAN KONSUMEN DI WAROENG SPESIAL SAMBAL âSSâ SAMPANGAN SEMARANG - Hana Nafisah Rokhmah, 13.05.51.0085 (Students Journal of Economic and Management, 2017)
This study entitled the effect of service quality, corporate image, perception of price and confidence customer of customer satisfaction on consumer Waroeng Spesial Sambal âSSâ Sampangan Semarang. The population in this study was customers in Waroeng Spesial Sambal âSSâ Sampangan Semarang. Sampling method used in this study was purposive sampling that technique determines the sample with particular consideration in accordance with the desired destination with the nomer of samples taken 100 respondents. The colleced data were analyze using factor analysis to test the validity of statement items, cronbach alpha of each partial independent variables were tested with the coefficient if determination and test fit the model to test and prove the influence of the partial each independent variable. The results of this study indicated that service quality, corporate image, and confidence customer of customer satisfaction on consumer. But the price of perception have negative effects significantly to customer satisfaction at Waroeng Spesial Sambal âSSâ Sampangan Semarang. Key words: Service Quality, Corporate Image, Price Perception, Confidence Customer, and Customer Satisfaction.